PERANCANGAN PROMOSI MAKANAN TRADISIONAL LAPEK KAMPUANG ARO KHAS LUBUK ALUNG MELALUI MEDIA BILLBOARD - ELKHAIRATIL FADILA, Drs. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Traditional food promotion planning Lapek Aro Kampuang aims to introduce Lapek Kampuang Aro so that food can be more widely known by the public and tourists as one of the typical souvenirs Lubuk Alung. Data in designing collected through observation, interviews as well as from the print and electronic media were then analyzed with methods of analysis 5W+1H to help solve problems and spark ideas. This design produces promotional media such as outdoor media namely billboards with design style parody. Besides the media campaign is also equipped with a supporting media such as Posters, X-Banner, Plastic Shopping Bags, Hang Tags, Flyers and Merchandise (Pin, Mug, Keychain, Calendars, Tshirts).Keywords : Promotions, Traditional, Lapek Kampuang Aro, Billboard, Parodi